Teaching Students about Education for Sustainable Development through E-module of Indonesian Traditional Fermented Food - Budiati, Andita Nur Sakinah Lili; Hernani, Hernani; Amprasto, Amprasto (FKIP Universitas Lampung, 2022)
The limitations of teaching materials that add values to Education for Sustainable Development (ESD) open up opportunities to develop supplementary teaching materials that integrate ESD with the latest information technology to support 21st-century skills. This study aims to develop a science e-module containing ESD theme of Indonesian traditional fermented food to build students' creative thinking skills, and sustainability awareness. The e-module development is carried out with the ADDIE development model. This study describes (1) a description of the development stages and (2) a description of the validation of the e-module in terms of mapping ESD aspects, creative thinking skills, and sustainability awareness, and a description of the validation of the e-module media display. The results of data analysis show that the results of data analysis show that the validation of mapping aspects of ESD and media obtained the categories of